A Buffer Stock Model to Ensure Price Stabilization and Availability of Seasonal Staple Foods under Free Trade Considerations - Sutopo, Wahyudi; Bahagia, Senator Nur; Cakravastia, Andi; Arisamadhi, T.M.A. (Journal of Engineering and Technological Sciences, 2012)
PriceÂ  volatilityÂ  andÂ  scarcityÂ  haveÂ  becomeÂ  aÂ  greatÂ  problemÂ  inÂ  the distributionÂ  systemÂ  ofÂ  seasonalÂ  stapleÂ  foodsÂ  producedÂ  byÂ  theÂ  agricultural industry.Â  ThereÂ  isÂ  aÂ  salientÂ  supplyÂ  disparityÂ  duringÂ  theÂ  harvestÂ  andÂ  planting seasons.Â  ThisÂ  conditionÂ  couldÂ  causeÂ  disadvantagesÂ  toÂ  stakeholdersÂ  suchÂ  as producers,Â  wholesalers,Â  consumers,Â  andÂ  government.Â  ThisÂ  paperÂ  proposesÂ  a bufferÂ  stockÂ  modelÂ  underÂ  free-tradeÂ  considerationsÂ  toÂ  substituteÂ  quantitative restrictionsÂ  andÂ  tariffsÂ  withÂ  anÂ  indirectÂ  marketÂ  interventionÂ Â  instrument.Â  This instrumentÂ  wasÂ  developedÂ  usingÂ  aÂ  bufferÂ  stockÂ  schemeÂ  inÂ  accordanceÂ  with Â a Â warehouse receipt systemÂ  (WRS) andÂ  aÂ  collateral management system.Â  AÂ  public serviceÂ  institutionÂ  forÂ  stapleÂ  foodÂ  bufferÂ  stockÂ Â  (BLUPP)Â  isÂ  proposedÂ  asÂ  the wholesalerâs competitor,Â  withÂ  as main responsibilityÂ Â  to ensure price stabilization and availability of staple food. Multi-criteria decision-making is formulated as a singleÂ  objectiveÂ  mixedÂ  integerÂ  non-linearÂ  programmingÂ  (MINLP)Â  model.Â  The resultsÂ  showsÂ  thatÂ  theÂ  proposedÂ  modelÂ  canÂ  beÂ  appliedÂ  toÂ  solveÂ  theÂ  distribution problemÂ  andÂ  canÂ  giveÂ  moreÂ  promisingÂ  outcomesÂ  thanÂ  itsÂ  counterpart,Â  direct market intervention.